Construction of Gross Human Rights Settlement Arrangements in the Framework of Justice and Legal Certainty in Indonesia - Ni Nyoman Putri Purnama Santhi; Anak Agung Gede Oka Wisnumurti; Ni Luh Made Mahendrawati; I Nyoman Gede Sugiartha (Journal Equity of Law and Governance, 2026)
This study examines the construction of regulatory frameworks for resolving gross human rights violations within the justice system and legal certainty in Indonesia. Despite existing legislation such as Law Number 26 of 2000 on Human Rights Courts, its implementation faces significant challenges including overlapping institutional authority, inadequate supporting legal instruments, and insufficient coordination among related agencies. The research analyzes primary legal sources including the 1945 Constitution, Law No. 26/2000 on Human Rights Courts as main national legal instruments and the few others international legal instruments, that supplemented by secondary sources from academic literature and journal articles. A deductive analytical approach is employed to test the harmony of applicable legal norms and assess whether existing regulations can realize the principles of justice and legal certainty in practice. The research highlights that addressing gross human rights violations requires not only robust criminal law enforcement, but also restorative justice approaches to ensure substantive justice for victims and comprehensive legal certainty. Therefore, regulatory and institutional reconstruction integrating national legal principles and international human rights standards is essential to enhance resolution effectiveness and provide optimal protection for victims.